2008
DOI: 10.1177/030089160809400308
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in Italy after Conservative Treatment of Early Breast Cancer. A Survey by the Italian Society of Radiation Oncology (AIRO)

Abstract: Although the quality of radiotherapy delivery has improved in Italy in recent years, approaches that do not conform to international standards persist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…In comparison with other RO surveys conducted in Italy in 2012 (lung cancer) and 2008 (breast and head/neck cancer), the number of responding centres was encouraging, being 45, 48 and 50%, as reported by Ramella et al (8), Aristei et al (9) and Frata et al (10), respectively. This finding reveals an increased sense of membership of radiation oncologists in the RO community and a willingness to deepen their knowledge of the Italian reality in order to improve the quality of their investigation.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…In comparison with other RO surveys conducted in Italy in 2012 (lung cancer) and 2008 (breast and head/neck cancer), the number of responding centres was encouraging, being 45, 48 and 50%, as reported by Ramella et al (8), Aristei et al (9) and Frata et al (10), respectively. This finding reveals an increased sense of membership of radiation oncologists in the RO community and a willingness to deepen their knowledge of the Italian reality in order to improve the quality of their investigation.…”
Section: Discussionmentioning
confidence: 45%
“…A main drawback of the present study was the number of responding centres that, although higher than in previous surveys (8)(9)(10), limited the analysis. Moreover, we cannot deny heterogeneity in our analysis due to different interpretations of survey queries.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, our interviewees reported that although the guidelines do not dictate what is covered and reimbursed by the national healthcare system, it is easier for hospitals to get reimbursement for procedures and pharmaceuticals when they conform to national guidelines (INT14). Studies suggest that adherence to guidelines varies, with underuse of chemotherapy, radiotherapy and hormonal therapy being evident (Aristei et al 2008;Sacerdote et al 2013).…”
Section: Legalmentioning
confidence: 99%